Assessment of H2S-Induced Cracking Susceptibility in Steam Line Pipes and Weld Zones During Geothermal Well Construction - Pragitta, Riene Kaelamanda; Pratesa, Yudha (UI Scholars Hub, 2025)
The susceptibility of steam line pipes, especially in the HAZ (heat-affected zone) and weldment areas, to hydrogen sulfide in the geothermal industry is crucial to understand from the early stages, particularly during construction. The combination of tensile stress from residual stresses after welding and metallurgical phase transformation makes the joint areas vulnerable to sulfide stress cracking. This condition becomes even more extreme when the equipment operates during the well stimulation phase. This research assesses the severity of H₂S-induced cracking using NACE MR0175 and ISO 15156-1 standards, focusing on the effects of pH and partial pressure of H₂S (pH₂S). The findings aim to provide insights into critical factors influencing H₂S cracking susceptibility and to enhance material integrity in geothermal systems. The result shows that while A106 Gr B steel generally meets sour service requirements, certain nodes within the geothermal facility exhibit a moderate risk of cracking under transient conditions. These results emphasize the importance of controlling fluid composition and implementing proper welding procedures to mitigate sulfide stress cracking (SSC).